Racing weight and resistance training: perceptions and practices in trained male cyclists - Hoon, M. W.; Haakonssen, E. C.; Menaspà, P.; Burke, L. M. (The Physician and Sportsmedicine, 2019)
Objectives: This study sought to investigate the perceptions and practices of achieving `race weight` in a population of trained male cyclists. A secondary focus was to investigate the use of gym-based strength training, a possible attenuator of the side effects associated with weight reduction.